Surface modulation of hierarchical MoS2 nanosheets by Ni single atoms for enhanced electrocatalytic hydrogen evolution - Zhang, Huabin (2020)
Surface modulation at the atomic level is an important approach for tuning surface chemistry and boosting the catalytic performance. Here, a surface modulation strategy is demonstrated through the decoration of isolated Ni atoms onto the basal plane of hierarchical MoS2 nanosheets supported on multichannel carbon nanofibers for boosted hydrogen evolution activity. X-ray absorption fine structure investigation and density functional theory (DFT) calculation reveal that the MoS2 surface decorated with isolated Ni atoms displays highly strengthened H binding. Benefiting from the unique tubular structure and basal plane modulation, the newly developed MoS2 catalyst exhibits excellent hydrogen evolution activity and stability. This single-atom modification strategy opens up new avenues for tuning the intrinsic catalytic activity toward electrocatalytic water splitting and other energy-related processes.